The role of vitamin D in prevention OF COVID-19 and its severity: an umbrella review: Vitamin D versus COVID-19: an Umbrella review - Margarucci, Lory Marika; Montanari, Enrico; Gianfranceschi, Gianluca; Caprara , Claudio; Valeriani, Federica; Piccolella, Antonio; Lombardi, Valentina; Scaramucci, Elena; Romano Spica, Vincenzo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim. Vitamin D is known to modulate immune response and its deficiency was associated with respiratory distress in patients hospitalized for pneumonia. Nevertheless, numerous reviews on vitamin D in COVID-19 patients have shown conflicting results, as previously reported also for other respiratory diseases (e.g., influenza). Methods. This umbrella review aims to assess whether low serum 25-OHD is associated with susceptibility to COVID 19, their severity, and mortality. A total of 1559 studies were excluded after the title, abstract and full-text articles screening and 9 papers were included in this review: 2 systematic reviews and 7 metanalysis. Results. The findings of this review that summarized studies from 5 WHO regions (European Region, Region of the Americas, South-East Asia Region, Eastern Mediterranean Region, Western Pacific Region) to exclusion only African region, show that low serum 25-OHD levels are associated with higher infection risks for COVID-19. Conclusions. Although the umbrella findings indicate a potential role of vitamin D deficiency in COVID-19 severity in hospitalized patients and showing an association between Vitamin D supplementation and COVID-19 severity, however, more robust data from randomized controlled trials are further needed to confirm a possible association with the mortality rates.